2011
DOI: 10.3892/ijo.2011.972
|View full text |Cite
|
Sign up to set email alerts
|

Frequent somatic demethylation of RAPGEF1/C3G intronic sequences in gastrointestinal and gynecological cancer

Abstract: Abstract. RAPGEF1 (also known as C3G and GRF2) is a guanine nucleotide exchange factor that releases GDP from the inactive Rap1 protein, facilitating its subsequent activation by the binding of GTP. Rap1 plays regulatory roles in proliferation, differentiation and apoptosis. Amplification and overexpression of RAPGEF1 have been found in small cell lung cancers, suggesting an oncogenic role. In contrast, hypermethylation of a promoter CpG island (CGI-A) of RAPGEF1 has been reported in squamous cervical tumors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…9 Interestingly, T. gondii is known to transactivate HERVs, including HERV-W elements, when infecting tumor cells, 62, 79 which would also fit with a co-factor triggering HERV-W activation with subsequent genetic and inflammatory effects related to HERV-W envelope. This points to an indirect role of such infectious agents through ‘epigenetically susceptible' HERV elements, as it is known that tumor cells have extensive DNA hypomethylation, 80, 81 which occurs physiologically in embryonic cells. 82 Thus, T. gondii could induce a targeted activation of HERV-W elements creating a risk for SZ or BD in individuals carrying an HERV-W ‘pathogenic element'.…”
Section: Discussionmentioning
confidence: 99%
“…9 Interestingly, T. gondii is known to transactivate HERVs, including HERV-W elements, when infecting tumor cells, 62, 79 which would also fit with a co-factor triggering HERV-W activation with subsequent genetic and inflammatory effects related to HERV-W envelope. This points to an indirect role of such infectious agents through ‘epigenetically susceptible' HERV elements, as it is known that tumor cells have extensive DNA hypomethylation, 80, 81 which occurs physiologically in embryonic cells. 82 Thus, T. gondii could induce a targeted activation of HERV-W elements creating a risk for SZ or BD in individuals carrying an HERV-W ‘pathogenic element'.…”
Section: Discussionmentioning
confidence: 99%
“…In human carcinogenesis, the C3G gene appears to play a crucial role by itself. Alteration of the C3G genetic activity via amplification or methylation is associated with several cancers such as lung, gastrointestinal and gynecological cancers [33], [34]. Although it is not exactly well known whether the genetic variants of the Dock180 and C3G gene are linked to gastric carcinogenesis, our study suggests several SNPs in these genes, especially rs4635002 and rs7853122, are significantly associated with risk of gastric cancer, and thus may be a susceptible gene in the development of gastric cancer.…”
Section: Discussionmentioning
confidence: 64%
“…Recent data also suggested that C3G, acting through Rap1, induces invasion of epithelial ovarian cancer cells and promotes the secretion of matrix metalloproteases MMP2 and MMP9 [20]. In colon carcinoma, the C3G gene is frequently demethylated [21], but it remains to be determined whether this epigenetic modification is associated with changes in C3G expression or if it plays any relevant role in the progression of this cancer.…”
Section: Introductionmentioning
confidence: 99%